Transparency and Liquidity: A Study of Block Trades on the London Stock Exchange Under Different Publication Rules. - Gemmill, Gordon (Journal of Finance, 1996)
This article examines whether reducing a market's transparency, by delaying the publication of prices for block trades, has any impact on liquidity. The analysis uses a sample of 5,987 blocks from the London Stock Exchange that cover three different publication regimes: immediate (1987/88), ninety minutes (1991/92), and twenty-four hours (1989/90). Delaying publication does not affect the time taken by prices to reach a new level, which is rapid under all regimes. Spreads differ across years but their size relates more closely to market volatility than to speed of publication. There is, therefore, no gain in liquidity from delayed publication.